Opini Auditor Dan Solvabilitas Sebagai Pemoderasi Pengaruh Profitabilitas Terhadap Audit Delay - Dewanto, I Gede Ari; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 24 No 3 (2018), 2018)
Audit delay is the time required by the auditor to generate audit reports on the performance of a company's financial statements. The purpose of this study is to obtain empirical evidence about auditor opinion and solvency as a moderator of profitability effect on audit delay. This research was conducted at a manufacturing company listed on the Indonesia Stock Exchange (IDX) with a period of research in 2013-2015. The method of determining the sample in this study using purposive sampling method with a sample of 165 manufacturing companies during the period 2013-2015 that already meet the criteria for determining the sample. Data analysis technique applied in this research is test of absolute difference value. The results showed that Profitability had a significant negative effect on audit delay. Auditor opinion strengthens the negative effect of profitability on audit delay. Solvency weakens the negative effect of profitability on audit delay. Keywords: Audit Delay, Profitability, Auditor Opinion, Solvency.